Involuntary Cure: Rebecca West’s The Return of the Soldier - Linett, Maren (Disability Studies Quarterly, 2013)
This article takes a disability studies approach to Rebecca West’s 1918 novel, The Return of the Soldier, the story of an amnesiac soldier returned from the Front. Such an approach highlights the extreme sanism of the novel’s ending, where the characters agree that if Chris were left in his amnesiac state, he “would not be quite a man.” This essay argues that although the novel initiates an incisive critique of sanism as a set of patriarchal and class-bound behavioral norms, it is unable to follow through on that critique. West’s ableism overrides the novel’s concern with the injustices of class, gender, and war, prompting the novel’s insistence that the “mad” soldier, Chris Baldry, be involuntarily cured. Keywords: Rebecca West, madness, shell-shock, disability